2017
DOI: 10.1002/eqe.2876
|View full text |Cite
|
Sign up to set email alerts
|

Conditional spectrum‐based ground motion record selection using average spectral acceleration

Abstract: Summary The use of a seismic intensity measure (IM) is paramount in decoupling seismic hazard and structural response estimation when assessing the performance of structures. For this to be valid, the IM needs to be sufficient;that is, the engineering demand parameter (EDP) response should be independent of other ground motion characteristics when conditioned on the IM. Whenever non‐trivial dependence is found, such as in the case of the IM being the first‐mode spectral acceleration, ground motion selection mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(145 citation statements)
references
References 36 publications
5
140
0
Order By: Relevance
“…To do so, we used the original algorithm developed for CS(SAT) [41] and its extended version for CS(AvgSA) [53]. To do so, we used the original algorithm developed for CS(SAT) [41] and its extended version for CS(AvgSA) [53].…”
Section: Ground Motion Databasementioning
confidence: 99%
See 1 more Smart Citation
“…To do so, we used the original algorithm developed for CS(SAT) [41] and its extended version for CS(AvgSA) [53]. To do so, we used the original algorithm developed for CS(SAT) [41] and its extended version for CS(AvgSA) [53].…”
Section: Ground Motion Databasementioning
confidence: 99%
“…Currently, in our opinion the most promising proposal is for employing the averaged spectral acceleration (AvgSA), whereby the logarithm of spectral acceleration is averaged over a range of periods [44][45][46][47][48], or other proposals for averaging spectral ordinates in the linear space [49,50]. Going one step further, Kohrangi et al [53] proposed a record selection method, termed CS(AvgSA), that improves upon the SAT-based CS approach, CS(SAT) [41], by changing the conditioning IM from spectral acceleration at a single period to AvgSA. Aiming instead at capturing the entire range of response that matters for loss estimation, Kazantzi and Vamvatsikos [52] proposed using AvgSA as a common, first-mode-period independent IM to assess the vulnerability for a whole class of buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Eads et al showed that Saavg is generally more efficient and more sufficient and provides more stable collapse risk estimates than Sa( 1 ) after evaluating the efficiency and sufficiency of a similar IM for collapse prediction using nearly 700 moment-resisting frame and shear wall structures of various heights [20]. A recasting of conditional spectrum record selection which is based on Saavg over a period range as the conditioning IM was presented by Kohrangi et al [21].…”
Section: Global Collapsementioning
confidence: 99%
“…If considerable difference exists among the different first mode periods, one should consider using two different definitions of AvgSa, one for low/mid-rise structures (shorter periods) and another for high-rise ones (longer periods), for better fidelity. In any case, ground motion records need to be selected for each definition of AvgSa at a given set of sites [12,13], while mean hazard curves are required for each definition of AvgSa and at each separate site.…”
Section: Verification Examplementioning
confidence: 99%